A BUCOLIC REMEDY OF FORMULATION AND EVALUATION OF POLYHERBAL HAIR OIL - U KASHID, SNEHAL (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The birth of cosmetics forms an incessant narrative throughout the past of man as they developed. The present study aimed to formulate polyherbal hair oil using various efficient herbs. Methods: Hair oil formulation of Cocos nucifera (oil), Ricinus communis (oil), Brassica juncea (oil), Trigonella foenum-graecum (Seeds), Murraya koenigii (Leaf), Hibiscus rosa-sinensis (Flowers), Nigella sativa (seeds), and Cinnamomum camphora in the form of polyherbal oil using boiling method. These ingredients are rich in various phytochemicals, vitamins, proteins, antioxidants, and so many other constituents which are important for the growth and rejuvenation of the hair cycle. Evaluation of hair oil carries out by various parameters such as sensitivity test, acid value, saponification value, phytochemical screening, pH, specific gravity, viscosity, and irritation test. Results: All the values of evaluation are within the acceptable limit. As compared to market formulations, this herbal oil having minimal or zero adverse effects. Conclusion: It is concluded that formulated hair oil boost hair growth, decrease hair fall, dandruff, gray hair, and gives lustrous and shiny hairs.